The Effect of Dogmatic Thinking on Emotional Creativity: The Mediating Role of Self-Compassion in University Students - Nikzad Tehrani, Fatemeh; Soghra Sina, Fatemeh (KMAN Counseling & Psychology Nexus, 2026)
The aim of the present study was to examine the effect of dogmatic thinking on emotional creativity, considering the mediating role of self-compassion, among students at the Islamic Azad University, Neka Branch. This study was applied in terms of purpose. In terms of data collection, it was field-based, and regarding data gathering and analysis, it was descriptive and correlational, using a structural equation modeling approach. The statistical population included all students of the Islamic Azad University, Neka Branch, in the 2024–2025 academic year (N = 1,935). To determine the sample size, the Krejcie and Morgan table was used, and 321 students were selected through stratified random sampling based on academic level. The data collection instruments comprised three standard questionnaires: the Dogmatic Thinking Questionnaire by Younesi and Mirafzal (2008), the Emotional Creativity Questionnaire by Averill and Thomas-Knowles (1991), and the Self-Compassion Scale by Neff (2003). Data were analyzed in two parts: descriptive statistics (frequency, percentage, and charts) and inferential statistics (the Kolmogorov–Smirnov test and structural equation modeling) using SPSS and AMOS software. The results indicated that dogmatic thinking affects emotional creativity and self-compassion in students. In addition, self-compassion affects emotional creativity in students. Furthermore, the findings showed that self-compassion mediates the relationship between dogmatic thinking and emotional creativity in students.